Analysis of Flutter Characteristics for Composite Laminates in Hypersonic Yawed Flow - Shuang Cao; Tongqing Guo; Jiangpeng Wu; Di Zhou; Ennan Shen (Aerospace)
This paper investigates the flutter characteristics of composite laminates in hypersonic yawed flow using numerical simulations. The governing equations are derived based on Hamilton’s principle and were discretized using the assumed mode method. The unsteady aerodynamic force is calculated by using the piston theory, including the influence of the yaw angle. Several laminate models are designed to study the effects of the stacking sequence, thickness ratio, and fiber orientation on the critical dynamic pressure and the amplitude of the limit cycle oscillation. Numerical results show that positioning the material with higher stiffness on the upper layer can lead to a higher critical dynamic pressure and a smaller amplitude of the limit cycle oscillation. In the case of large yaw angles, increasing the thickness of the material with larger stiffness can clearly suppress the amplitude of the limit cycle oscillation. Fiber orientation symmetry to the x-axis can improve the flight stability with the change in the yaw angle.